Teacher's Perspective: Implementation of Online Learning during the Covid-19 Pandemic - Sudewiputri, Made Padmarani; Dewi , Md Sri Astika (Universitas Pendidikan Ganesha, 2022)
The Covid-19 pandemic has caused a major transformation in various fields of life. One of them is the transformation of face-to-face learning into online learning. This study aims to analyze the online learning process and the supporting and inhibiting factors for teachers in carrying out online learning during the Covid-19 pandemic. This research uses a qualitative descriptive research method. The subjects used in this study were elementary school fifth-grade teachers. Data collection techniques used in this study were open questionnaires, semi-structured interviews, documentation, and field notes. Data analysis was carried out qualitatively through a reduction and verification process. The results and discussion of this study indicate that online learning is less effective for teachers, especially for learning at the elementary school level. This is because learning carried out online makes teachers feel less than optimal in providing learning material so that the material is incomplete. In addition, using learning media in online learning is also not optimal. Based on the results of this research, further studies need to be conducted to evaluate the implementation of online learning in elementary schools to obtain the right solution to deal with the problems that occur.